2023
DOI: 10.1002/imhj.22083
|View full text |Cite
|
Sign up to set email alerts
|

Framing the work: A coparenting model for guiding infant mental health engagement with families

James McHale,
Herve Tissot,
Silvia Mazzoni
et al.

Abstract: When working with families of infants and toddlers, intentionally looking beyond dyadic child‐parent relationship functioning to conceptualize the child's socioemotional adaptation within their broader family collective can enhance the likelihood that clinical gains will be supported and sustained. However, there has been little expert guidance regarding how best to frame infant‐family mental health therapeutic encounters for the adults responsible for the child's care and upbringing in a manner that elevates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Their objectives are to offer guidelines to practitioners for infant-family intake assessments that can reliably and validly capture core coparenting features of engagement, teamwork, conflict, and child focus. Central to this work is guidance for the use of ecomaps to chart the functional members of the infant or toddler's coparenting system, observational assessments centred by the LTP, self-reflections of coparenting using a coparenting scale and separate evaluations of the child and their symptomatology provided by each coparent (McHale et al, 2023).…”
Section: Coparenting In Case Conceptualisationmentioning
confidence: 99%
“…Their objectives are to offer guidelines to practitioners for infant-family intake assessments that can reliably and validly capture core coparenting features of engagement, teamwork, conflict, and child focus. Central to this work is guidance for the use of ecomaps to chart the functional members of the infant or toddler's coparenting system, observational assessments centred by the LTP, self-reflections of coparenting using a coparenting scale and separate evaluations of the child and their symptomatology provided by each coparent (McHale et al, 2023).…”
Section: Coparenting In Case Conceptualisationmentioning
confidence: 99%
“…The idea was to propose a set of guidelines, including procedures, that any clinician, regardless of training, experience, therapeutic orientation or work habits, could use in their practice with families and young children, in addition to what they usually do with families, whether it be individual or dyadic work. Dubbed 'framing the work' (FTW; McHale et al, 2023), this set of guidelines comprises assessment, monitoring, and brief intervention procedures targeting coparenting and whole family relationships. An ideal application of the protocol would be to dedicate a couple of sessions to the thematic of coparenting at intake, as well as near the end of therapy.…”
Section: T H E Lt P a S A CL I N Ic A L Toolmentioning
confidence: 99%
“…In family life, the quality of coparenting serves as a critical cornerstone influencing the socialization process of young adolescents [27,41,42]. Existing research has demonstrated that parental coordination, open communication and conflict resolution positively contribute to adolescents internalizing behavioral guidelines both at home and in school [43]. This, in turn, enhances the adaptive emotional regulation capacities of adolescents [41,44], bringing about a decline in adolescent depression [45,46].…”
Section: Introductionmentioning
confidence: 99%